Comments on the Methodology of Teaching Uzbek Phonetics - Dildora Sagdullaevna Ganieva (Researchparks Publishing, 2021)
The purpose of the study of phonetics is to study the system of sounds in the native language, mainly the perfect mastery of pronunciation norms, as well as the formation of correct writing skills, increase students' vocabulary, word-to-speech correct and appropriate use, expressive reading of poetic works and mastery of the first secrets of artistic creation.